DAYA TAHAN KARDIORESPIRASI SISWA PEMAIN BASKET SEKOLAH MENENGAH ATAS DI KOTA DENPASAR LEBIH BAIK DARI PADA SISWA BUKAN PEMAIN BASKET - Dewi, Anak Agung Fridami; Muliarta, Made (E-Jurnal Medika Udayana; Vol 5 No 4 (2016): E-jurnal medika udayana, 2016)
CARDIORESPIRATORY ENDURANCE AMONG SENIOR HIGH SCHOOL BASKETBALL PLAYERS IN DENPASAR IS BETTER THAN NON-BASKETBALL PLAYER STUDENTS ABSTRACT Basketball game requires a good cardiorespiratory endurance, thus cardiorespiratory endurance can be measured by maximal oxygen capacity (VO2max). Cardiorespiratory endurance can improve with routine physical exercise that meet the required amount of duration and intensity, including basketball training. The objective in this study is to compare the cardiorespiratory endurance of senior high school male basketball players and non-basketball players student in Denpasar. This is an analytic study with cross sectional approach. The samples were 24 students and taken by purposive sampling which is consist of basketball and non-basketball group. Cardiorespiratory endurance is measured by calculating the VO2max from Cooper Test 2,4 km. The mean VO2max is higher in basketball player which is 45,906 ml/kg/minute than in non basketball player which is 36,603 ml/kg/minute. The mean difference is 9,303 ml/kg/minute, with 95% confidence interval lower is 6,308 and upper is 12,299. There is a significant difference (p=0,000) between the cardiorespiratory endurance of Senior high school male basketball player and non-basketball player student in Denpasar using independent t-test. This study suggests that senior high school students should do routine physical exercise to improve a better cardiorespiratory endurance, including playing basketball. Further research in larger scale is needed.
Keywords: Basketball player, nonbasketball player, cardiorespiratory endurance, VO2max, Cooper Test 2,4 km.